Eutrophication decrease: Phosphate adsorption processes in presence of nitrates - Boeykens, Susana Patricia (2017)
Eutrophication causes aquatic environment degradation as well as serious problems for different purposes of water uses. Phosphorus and nitrogen, mainly as phosphate and nitrate respectively, are considered responsible for eutrophication degradation. The focus of this work was the study of adsorption processes for decreasing phosphate and nitrate concentrations in bi-component aqueous systems. Dolomite and hydroxyapatite were selected as low-cost adsorbents. Obtained results showed that both adsorbents have high capacity for phosphate adsorption which the presence of nitrate does not modify. Hydroxyapatite proved to be the most efficient adsorbent, however, it showed a low percentage of desorption and few possibilities of reuse. Dolomite, on the other hand, allows a desorption of the adsorbed material that favours its reuse.